PENERAPAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Deni Muliani; Arwin Arwin; Nelly Astimar (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
AbstractThe purpose of this study was to describe the aplication of Cooperative Learning type Think Pair Share model to improve student learning outcomes in social studies learning. This research is Classroom Action Research which uses qualitative and quantitativw approaches. The subjects of this study were twenty five teachers and fifth grade students. The implementation of this research was carried out in two cycle with research procedures consisting of planning, implementation, oservation and reflection. The results showed an increase: a) RPP cycle I an average value of 83,9%, cycle II average 92,8%, b) Implementation of teacher aspects and aspects of students cycle I average value 79,7%, cycle II average value 93,7%, c) Student learning cycle I an average value of  77,7%, cycle II an average value of 86,7%. Thus, the aplication of the Cooperative Learning type Think Pair Share model can improve learning outcomes student in social studies learning in Class V of Padang Besi Elemenntary School 08 Padang.Keywords: Think Pair Share, Learning Outcomes; Social science